Using games to trigger collective changes in natural resource management: Conceptual foundations for behavioral change - Falk, Thomas; Zhang, Wei; Meinzen-Dick, Ruth S.; Bartels, Lara (2021)
By Thomas Falk, Wei Zhang, Ruth Meinzen-Dick, and Lara Bartels